The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/2016jd026032
|View full text |Cite
|
Sign up to set email alerts
|

Black carbon aerosol and its radiative impact at a high‐altitude remote site on the southeastern Tibet Plateau

Abstract: Aerosol black carbon (BC) was measured with an Aethalometer™ at Lulang, a high‐altitude station in southeastern Tibetan Plateau (TP), from July 2008 to August 2009. Daily mean BC loadings varied from 57.7 to 5368.9 ng m−3 (grand average ± standard deviation = 496.5 ± 521.2 ng m−3), indicating a significant BC burden even at free tropospheric altitudes. BC loadings were highest during the premonsoon and lowest during the monsoon, and peaks in BC were coincident with high atmospheric boundary layers. Daily peaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 100 publications
(128 reference statements)
3
21
0
Order By: Relevance
“…An intensive measurement campaign was conducted from Figure 1. Black carbon concentrations (µg m −3 ) measured at 15 sampling sites in the Himalayas and on the Tibetan Plateau based on the measurements from this study (blue solid circles) and other studies (black solid circles) from Ma et al (2003), Pant et al (2006), Marinoni et al (2010), Stone et al (2010), Babu et al (2011), Engling et al (2011, Li et al (2017), Wan et al (2015), Wang et al (2015a), M. Wang et al (2016), Zhu et al (2016), and Raatikainen et al (2017). More detailed information concerning these studies is summarized in Table S1.…”
Section: Sampling Sitementioning
confidence: 96%
See 2 more Smart Citations
“…An intensive measurement campaign was conducted from Figure 1. Black carbon concentrations (µg m −3 ) measured at 15 sampling sites in the Himalayas and on the Tibetan Plateau based on the measurements from this study (blue solid circles) and other studies (black solid circles) from Ma et al (2003), Pant et al (2006), Marinoni et al (2010), Stone et al (2010), Babu et al (2011), Engling et al (2011, Li et al (2017), Wan et al (2015), Wang et al (2015a), M. Wang et al (2016), Zhu et al (2016), and Raatikainen et al (2017). More detailed information concerning these studies is summarized in Table S1.…”
Section: Sampling Sitementioning
confidence: 96%
“…However, several recent studies showed that the impact of internal Tibetan sources (e.g., yak dung combustion by local residents) on the atmosphere of the TP should not be overlooked (Chen et al, 2015;Li et al, 2016a;. In the past few decades, a number of field campaigns conducted on the TP have investigated the concentrations, sources, and spatial and temporal variations of BC aerosol (e.g., Engling et al, 2011;Cong et al, 2015;Zhu et al, 2016;Wang et al, 2017;. Recently, research has begun to focus on the light absorption characteristics of BC particles in the atmosphere and snow (Li et al, 2016b, c;.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing concern that glaciers on the TP are in retreat, due in part to the influence of atmospheric black carbon (BC) and dust which are light‐absorbing materials (William et al, ). The optical properties and radiative effects of these two substances have been well documented over the past decades (e.g., Qu et al, ; Wang, Cao, Han, Tian, Zhang, et al, ; Wang, Cao, Han, Tian, Zhu, et al, ; Zhang et al, ; Zhao, Wang, et al, ). More recently, a group of colored organic compounds, collectively known as brown carbon (BrC), has been found to absorb sunlight, especially at short wavelengths (Andreae & Gelencsér, ).…”
Section: Introductionmentioning
confidence: 99%
“…An intensive measurement campaign was conducted from Figure 1. Black carbon concentrations (µg m −3 ) measured at 15 sampling sites in the Himalayas and on the Tibetan Plateau based on the measurements from this study (blue solid circles) and other studies (black solid circles) from Ma et al (2003), Pant et al (2006), Marinoni et al (2010), Stone et al (2010), Babu et al (2011), Engling et al (2011), Zhao et al (2012), Li et al (2017), Wan et al (2015), Wang et al (2015a), M. Wang et al (2016), Zhu et al (2016), and Raatikainen et al (2017). More detailed information concerning these studies is summarized in Table S1.…”
Section: Sampling Sitementioning
confidence: 96%